Potensi Beberapa Susu Fermentasi Komersial Sebagai Antifungi Candida albicans - Nunung Sulistyani, Nur Khikmah (Universitas Atma Jaya Yogyakarta, 2017)
Candida albicans cause opportunistic infection of the oral cavity. Probiotic has health benefits, produces organic acids as anti-C. albicans. The aim of this research was to determine the antifungal activity of commercial fermented milk products against Candida and viability of bacteria in commercial fermented milk products. The antifungal activity was determined using well diffusion method. Viability of lactic acid bacteria was done by plate count method. The results show that commercial fermented milk productshas an activity of anti-C.albicans were shown by irradical zone formed around well containing fermented dairy products. Viability of lactic acid bacteria 107-1010 CFU/mL.